Road Use Pattern and Street Crossing Habits of Schoolchildren in India - Tiwari, Rajnarayan R.; Patel, Shruti; Soju, Annie; Trivedi, Prarthana (Frontiers in Public Health, 2021)
Road traffic accidents contribute significant DALYs in global burden of diseases. The vulnerable group particularly the pedestrians and children are at increased risk. Road use pattern, street crossing habits and road safety awareness are important determinants of road traffic accidents. The present study was carried out to assess the road use pattern and street crossing habits of school children. This cross-sectional study included 497 school children of age 12-15 years. Interview technique was used as a tool for data collection on predesigned questionnaire. 40.4% school children did not like to go school alone and want somebody from family to drop them to school. About one quarter of the students were afraid of traffic and expressed their inability to deal with traffic on road. 10.7% reported crossing street in group and 1.4% reported running while crossing the street. Only 80.9% students received some form of road safety training and the parents and schools were the major source of information for such safety training. Age <14 years and lower level of mother’s education were found to be significant contributors for the poor road crossing habit in univariate as well as multivariate analysis. The study suggests that the knowledge regarding safe road use and street crossing was lacking among study participants albeit in small proportion only. Safety aspects can be partly strengthened by imparting practical knowledge about road use pattern, street crossing habits and road safety procedures.